PENGARUH RASIO KEUANGAN TERHADAP PERTUMBUHAN LABA PADA PT KRAKATAU STEEL (PERSERO) TBK PERIODE 2010-2014 - Ariani Dwi Yahya (Sains: Jurnal Manajemen dan Bisnis, 2018)
Analysis of financial reports is indispensable for the understanding of financial reporting information. The report laba-rugi, which listed the profit or loss that the company is one of the main financial statements of companies that reported results of activities within a certain period to profit while the balance sheet lists the source power company. This research aims to know the influence of current Ratio, total debt to total assets ratio, return on investment and total asset turnover against a profit growth of PT Krakatau Steel (persero) Tbk on 2010-2014 year, and aims to find out profit growth of PT Krakatau Steel (Persero) Tbk in 2010-2014. The methods used in this research is a case study of time series methods (timeframe, so that data can be found and a description of the relationships between variables). His variables independent variables namely divided on financial ratio (current ratio, total debt to total assets ratio, return on investment) and a dependent variable i.e. profit growth.         Statistical test results or partial test shows the variable current ratio there is no influence between current ratio against the profit growth. Variable total debt to total assets ratio there is influence between the Total debt to total asset ratio against the profit growth. Variable return on investment there is no influence between return on investment against profit growth. Variable total asset turnover there was no influence between total asset turnover against profit growth at PT Krakatau Steel (Persero) Tbk 2010-2014 Period. It is also supported by the determination of the coefficient indicates that the increase and decrease of 85.7% profit growth can be explained by the magnitude of the financial ratios on the company. The remaining 14.3% is affected by other variables not in this study.